Strategi Pemasaran Syariah Dalam Meningkatkan Penjualan Es Krim Miami Pada Agen di Karya Jaya Kota Palembang - Destri Aktarina; Suryati Suryati; Emi Puspita Dewi (ScidacPlus, 2024)
This research aims to find out how sharia marketing strategies increase Miami ice cream sales to agents in Karya Jaya and find out the inhibiting factors in marketing Miami ice cream sales to agents in Karya Jaya. In this research, the method used is a qualitative method, namely a type of field research with a qualitative descriptive approach. The data collection techniques used in this research are observation, interviews and documentation. The results of the research show that the sharia marketing strategy of the Miami Karya Jaya ice cream agent, namely the 4P marketing mix of product, price, place and promotion, has been implemented well and has also been imitated by the Miami Karya Jaya ice cream agent. The characteristics of the Prophet Muhammad SAW that made him successful in business were shiddiq (honest or true), amanah (trustworthy), fathanah (intelligent), and tabligh (communicative). Factors inhibiting sales of Miami ice cream are weather factors, damaged refrigerators, competition factors, and Miami ice cream melting.